Prosedur Pendaftaran Pajak Bumi Dan Bangunan Pedesaan Dan Perkotaan Pada BPKPAD Humbang Hasundutan - Junaidi Junaidi; Ompon Lastiur Sianipar; Sumaizar Sumaizar (SEKOLAH TINGGI AKUNTANSI DAN MANAJEMEN INDONESIA (STAMI), 2021)
The purpose of this study was to determine the analysis of the registration procedure for the Rural and Urban Land and Building Tax BPKPAD Humbang Hasundutan. Data collection techniques used by the author are interview techniques and direct observation. Sources of data from this study are tax officials and officers in the relevant department as well as any parties who are directly and indirectly related. The central tax is a levy by the central government and is used to finance state households. Meanwhile, local taxes are local government levies which, according to regulations, are used to finance regional expenditures. One of the efforts to improve the capacity of quality in the field of local government implementation funding for development is to increase and explore every existing potential. Regional taxes participate in financing regional development, without local taxes, the need for development will be difficult to fulfill. The analysis technique used is a qualitative method with the Miles and Huberman approach. The results of this study are that the tax registration procedure in Humbang Hasundutan has followed the SOP.